Inquiry Into Graduate Attributes: Reviewing the Formal and Informal Management Curricula. (August 2019) - Allen, Dee; Simpson, Colin
This article is aimed at any departmental faculty or head of school in charge of conducting curriculum review and presents a holistic approach based on Appreciative Inquiry and recently used by a University Business School in the Southwest of England. As a future-facing or strength-based approach, our Inquiry into Graduate Attributes brought together students, academics, employers, and employment consultants to agree on the most desirable generic attributes of business management graduates 5 years into the future, and to propose changes to course content, assessment, and cocurricular activities in line with these. The Inquiry into Graduate Attributes approach provides a methodological model for integrating the expectations of different stakeholder groups while acknowledging the various ways in which understandings of knowledge and outcomes are related to disciplinary epistemology. For researchers interested in the use of Action Research in the process of curriculum review, this article presents a relatively novel use of an applied Appreciative Inquiry technique, which we hope will initiate a broader conversation around the dynamics and reflective practices of curriculum design.